REFORMING AND DEVELOPING ACCOUNTING IN THE REPUBLIC OF KAZAKHSTAN - B.A. Alibekova,; B.A. Zhumatayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
Purpose of the study – study of the history of the reform and development stages of accounting of sovereign Kazakhstan. Methodology – general scientific research methods, such as induction and deduction, theoretical generalization, scientific abstraction were used in the study. Originality/Value – the value of the research is revealing the main trends in the development of domestic accounting regulation for the years of independence of the republic. The authors studied the ways, stages of the evolution of the accounting system.For this purpose, legislative and other regulatory acts, by-laws of ministries and departments concerning the conceptual framework and the organizational and structural forms of the organization of accountingwere analyzed. Conclusions – accounting reform ensured the adequacy of the accounting system of Kazakhstan to the requirements and characteristics of a market economy, allowed to form a new conceptual apparatus corresponding to the current level of development of accounting science and world trends. The new accounting system, based on the widespread use of international financial reporting standards by most business entities, has made business structures more open and, therefore, preferred by domestic and foreign investors, which has a positive effect on raising the country's competitiveness in the international arena